2007
DOI: 10.1038/ismej.2007.21
|View full text |Cite
|
Sign up to set email alerts
|

Survival of genetically marked Escherichia coli O157:H7 in soil as affected by soil microbial community shifts

Abstract: A loamy sand soil sampled from a species-rich permanent grassland at a long-term experimental site (Wildekamp, Bennekom, The Netherlands) was used to construct soil microcosms in which the microbial community compositions had been modified by fumigation at different intensities (depths). As expected, increasing depth of fumigation was shown to result in progressively increasing effects on the microbiological soil parameters, as determined by cultivation-based as well as cultivation-independent (PCR-DGGE, PLFA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 26 publications
4
74
0
1
Order By: Relevance
“…These results suggested that either some fraction of the inoculated E. coli might have entered the viable but not culturable (VBNC) state, or died off during the studies (29,31). While antibiotic resistant E. coli strains have been previously used in soil studies (9,11,15,17,22,26), the present study showed that genotype-or strain-specific qPCR may be a more sensitive tool for monitoring microbial population densities in the soil environment.…”
Section: Field Release Of E Coli Ks7-nr Into Soilmentioning
confidence: 79%
See 1 more Smart Citation
“…These results suggested that either some fraction of the inoculated E. coli might have entered the viable but not culturable (VBNC) state, or died off during the studies (29,31). While antibiotic resistant E. coli strains have been previously used in soil studies (9,11,15,17,22,26), the present study showed that genotype-or strain-specific qPCR may be a more sensitive tool for monitoring microbial population densities in the soil environment.…”
Section: Field Release Of E Coli Ks7-nr Into Soilmentioning
confidence: 79%
“…Results from several studies have shown that various stresses influence the survival and growth of E. coli in soils, including: high and low temperature (11,21,25), limited moisture (1-3, 9, 21), variation in soil texture (25), organic matter content (1,5,11), solar radiation (30), and competition and predation (2,26). Topp et al (25) observed that E. coli was capable of growing in soils amended with autoclaved swine manure slurry.…”
mentioning
confidence: 99%
“…In this context, the microbial communities that established after soil fumigation were shown to determine the fate of the invading species, whereby reduction in microbial diversity due to progressively enhanced fumigation depths resulted in higher pathogen persistence in soil (21). Similarly, in 25 different manures, the decline rate of E. coli O157:H7 was negatively correlated with Enterobacteriaceae richness (22).…”
mentioning
confidence: 90%
“…After E. coli O157:H7 derivative strain T addition, we monitored the microcosms at different time points over a 60-d period, during which all cultivationdependent and -independent analyses were performed. The survival of strain T, expressed as the number of cfu g −1 dry soil, was then determined by selective dilution plating on tryptic soy agar (TSA) plus respective antibiotics, in accordance with van Elsas et al (21). E. coli counts were determined after 24 h incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation